The Initial configuration of the Road Networks and transport systems in colonial Michoacán. First half of 16th Century (Tzintzun, Revista de Estudios Históricos, 2016)
The paper makes an analysis of the irst road formation in the colonialera in Michoacán, from its prehispanic origins until the decadeof 1560. It describes how the prehispanic routes contributed to colonialexpansion and how Michoacán incorporated gradually a colonialnetwork of roads that would exceed their original prehispanic limits.With this development, the original roads experienced a process of enlargementthrough the introduction of new forms of animal transport,a transcendent event in the analysis of the transformation of roads.
Keywords: road networks; prehispanic networks; New Spain; Michoacán; 16th century